2003
DOI: 10.1037/1089-2680.7.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Affect Relationships: Models and Their Integrative Implications

Abstract: This article presents data from a number of areas of psychology that have dealt with the issue of whether positive and negative affects are independent—the bivariate view—or whether they operate inversely from each other—the unidimensional, bipolar view. Both models have extensive empirical support. A more integrative view, the Dynamic Model of Affect (DMA), specifies conditions under which both bivariate and bipolar models are valid. It is tailored to analyzing both affect systems functioning concurrently. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
210
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(238 citation statements)
references
References 94 publications
(103 reference statements)
19
210
0
4
Order By: Relevance
“…Simultaneously, it functions as a resource for positive short-and long-term outcomes in multiple life domains. The buffering effect of positive emotions is also central to another model that investigates the role of positive affect, the Dynamic Model of Affect developed by Zautra and colleagues (Zautra et al, 2001;Reich et al, 2003;Davis et al, 2004). The main assumption of this model is that positive affect has the strongest beneficial effects under conditions of high stress relative to low stressful situations.…”
Section: Broaden-and-build Theory: the Role Of Positive Affectmentioning
confidence: 99%
“…Simultaneously, it functions as a resource for positive short-and long-term outcomes in multiple life domains. The buffering effect of positive emotions is also central to another model that investigates the role of positive affect, the Dynamic Model of Affect developed by Zautra and colleagues (Zautra et al, 2001;Reich et al, 2003;Davis et al, 2004). The main assumption of this model is that positive affect has the strongest beneficial effects under conditions of high stress relative to low stressful situations.…”
Section: Broaden-and-build Theory: the Role Of Positive Affectmentioning
confidence: 99%
“…Foundational evidence for the adaptive function of positive affect is beginning to accrue, however (e.g., Bonanno & Keltner, 1997;Folkman, 1997;Fredrickson et al, 2003;Tugade & Fredrickson, 2004;Zautra, Johnson, & Davis, 2005). Reich, Zautra, and Davis (2003) reviewed a number of studies showing that positive affect, when present during times of stress, appear maximally effective at strengthening resistance. The finding that positive affect reduces vulnerability to stress has now been documented in different laboratory and field studies (e.g., Zautra, Reich, Davis, Potter, & Nicolson, 2000), under different stressful contexts (Ong, Bergeman, Bisconti, & Wallace, 2006;Zautra et al, 2005), and with different indices of health and well-being (e.g., Davis, Zautra, & Smith, 2004;Ong & Allaire, 2005).…”
Section: Research On the Role Of Positive Affect In The Stress Processmentioning
confidence: 99%
“…Therefore, given the known link between goal conflict and mixed emotions, it is plausible that mixed emotions participate in the process by which individuals achieve proposes that under conditions of low stress the affect system allows complex information processing, but under high stress, information processing is concentrated on immediate demands, and as a consequence, discrimination between positive affect and negative affect is simplified. Therefore, the DMA anticipates that high stress will result in negative correlations between positive affect and negative affect (Reich et al, 2003). Importantly, the DMA also predicts that individual differences in the capacity to experience more complex affective patterns (i.e., mixed emotions) during stressful situations may be beneficial for individuals' health (Davis, Zautra, & Smith, 2004;Reich et al, 2003).…”
mentioning
confidence: 99%
“…Therefore, the DMA anticipates that high stress will result in negative correlations between positive affect and negative affect (Reich et al, 2003). Importantly, the DMA also predicts that individual differences in the capacity to experience more complex affective patterns (i.e., mixed emotions) during stressful situations may be beneficial for individuals' health (Davis, Zautra, & Smith, 2004;Reich et al, 2003).Individual differences in mixed emotions are thought to buffer or moderate the negative consequences of stressful events on individuals' health (Reich et al, 2003). Thus, for example, some evidence has demonstrated that individual differences in experiencing mixed emotions are associated with levels of resilience during bereavement (Coifman, Bonanno, & Rafaeli, 2007).…”
mentioning
confidence: 99%